Cost- of- Illness Analysis of Type 2 Diabetic Patients in a Multispeciality Hospital at Coimbatore - D, Chidambaram; A, Ajith; KSG, Arulkumaran; TR, Sivagnanam (Indian Journal of Pharmacy Practice)
The prevalence and the number of people living with diabetes in India is increasing every year, which imparts a burden on the economic growth. The studies related to the healthcare cost of diabetes are limited in India. A prospective observational study was carried out for a period of seven months with the aim to determine average annual per patient direct cost for management of type 2 diabetes mellitus, to determine the average annual per patient direct cost for diabetic patients having micro and macro vascular complications, and the factors affecting the healthcare cost. The average annual per patient direct cost for management of type 2 diabetes is 38,589 rupees. Diabetes patients who did not have any complications spent 15,512 rupees as average annual per patient direct cost for their care. Patients with one complication spent 25,228 rupees as average annual per patient direct cost for their care. Patients with three complications spend 52,607 rupees as average annual per patient direct cost for their care. The factors affecting healthcare cost and hospitalization were the medicine cost, lab investigation cost, hospital admission cost, presence and severity of diabetes associated complications. Cost of illness studies can provide a framework for estimation of cost estimation for Cost Effectiveness and Cost Benefit Analysis, the methods which are commonly employed for decision making while updating the formulary. Pharmacist can perform his role when making formulary decisions as a member of Pharmacy and Therapeutic Committee (PTC), using the information gathered from pharmacoeconomic evaluation.
Keywords: Diabetes Mellitus; Pharmacoeconomics; Healthcare Cost; Cost of Illness; Direct Cost; Annual Medicine Cost; Annual Lab Cost; Annual Consultation Cost